2023
DOI: 10.1038/s41562-023-01733-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the global prevalence and determinants of COVID-19 vaccine acceptance and uptake in people living with HIV

Sahabi Kabir Sulaiman,
Muhammad Sale Musa,
Fatimah Isma’il Tsiga-Ahmed
et al.

Abstract: People living with HIV (PLHIV) are at higher risk of poor outcomes of SARS-CoV-2 infection. Here we report the pooled prevalence of COVID-19 vaccine acceptance/uptake and determinants among this vulnerable population of PLHIV based on a systematic review and meta-analysis of studies published by 25 August 2023. Among the 54 included studies (N = 167,485 participants), 53 (N = 166,455) provided data on vaccine acceptance rate, while 27 (N = 150,926) provided uptake data. The global prevalences of COVID-19 vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 146 publications
0
3
1
Order By: Relevance
“…The main finding of our study was the low coverage of vaccination (only slightly more than half) among PLWH. Our finding is slightly lower than a global COVID-19 vaccine uptake among PLWH of 56.6%, but at the same time notably lower than the rate of 90.1% for the European Region as reported by Sulaiman et al [ 6 ]. When considering the broader context, our findings also underscore a significant gap compared to the global vaccine uptake among the general population, which stands at a higher rate of 70.6% [ 28 ].…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…The main finding of our study was the low coverage of vaccination (only slightly more than half) among PLWH. Our finding is slightly lower than a global COVID-19 vaccine uptake among PLWH of 56.6%, but at the same time notably lower than the rate of 90.1% for the European Region as reported by Sulaiman et al [ 6 ]. When considering the broader context, our findings also underscore a significant gap compared to the global vaccine uptake among the general population, which stands at a higher rate of 70.6% [ 28 ].…”
Section: Discussioncontrasting
confidence: 80%
“…In-depth interviews, during which unvaccinated respondents mostly talked about the uselessness of COVID-19 vaccines since they could quickly recover from the mild disease with no complications, also confirmed these findings. A systematic review and meta-analysis conducted by Sulaiman et al reported association of perceived high susceptibility to SARS-CoV-2 infection and a strong belief in the vaccine’s effectiveness and utility with higher COVID-19 vaccine acceptance and uptake among PLWH [ 6 ]. HBM constructs, such as perceived severity of COVID-19 infection and perceived benefits of a COVID-19 vaccine have also been linked to vaccination acceptability among general population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations